Evaluasi IT Governance pada Sistem Elektronik Evaluasi Dosen Oleh Mahasiswa (E-EDOM) Dengan Menggunakan Framework Cobit 5 - Hadi Asnal; Muhamad Jamaris (Jurnal Teknologi Terpadu, 2018)
College of informatics and computer management - Amik Riau (STMIK Amik Riau) has electronic lecturer evaluation system by students (E-EDOM). The problems found in the System (E-EDOM) is the lack of ready students especially the new students STMIK Amik Riau in accepting changes in the evaluation system, this is due to not yet familiar new students, especially students from the region with the use of electronic systems, the server that resulted in the web server must follow the changes because the old source code will no longer recognize the system so it needs improvement that will affect the lecturer's evaluation process. In addition, E-EDOM STMIK Amik Riau has not previously been done evaluation of information technology governance. Based on this, the authors apply the evaluation of IT Governance according to COBIT standard 5. This research focus on BAI07 process (Management of Admission Change and Transition). The purpose of this research is to know the capability level of E-EDOM system in Transform and Transition Admission Management process. The research stages are based on the Assessment Process Activities of COBIT 5. The results of this study are audit results / audit reports of E-EDOM system, scientific publication in national journals,as well as enrichment of teaching materials on the information technology audit course.